Bilateral orbital-fronto-nasal osteoma. Transcranial, extradural resection - Palma, Eduardo; Garbino, Carlos; Rodríguez Martínez, Ricardo; Cheguhen, Gabriel (Cirugía del Uruguay, 1972)
1) A gigantic front etmoidal bilateral osteoma of the eyesocket, with right predominance, slow evolution '.nd few functional disturbances, is described. 2) Total resection of the osteoma was made througb a special technique of broad transcraneal approach; eye structures were preserved with all their annexecs; visual and nasal functions were restored to normal. 3) The technique employed is described, with stress on the advantages of this broad transcraneal extradural approach.